La desigualdad como realidad histórica y vivencia social y humana: De Thomas Piketty a Alec MacGillis y Matt Taibi.: Reseña y análisis crítico de cuatro libros (Revista Rupturas, 2023)
A critical reference to four books by three different authors is offered here: "Capital in the Twenty-First Century" and "Capital and Ideology", by the French economist Thomas Piketty; "The Divide: American Injustice" and "Fulfillment. Winning and Losing in One-Click America", whose authors are, respectively, Matt Taibbi and Alex MacGillis, both journalists, citizens from the United States. The purpose of this paper is to show what the four books have in common, as the central theme that concerns their authors is social inequality. From there, the central objective of this bibliographic review, is to demonstrate the relationship of complementarity that exists between the two works of Piketty, and the works of MacGillis and Taibbi. In the first case, the approach is scientific, it is based on an enormous background of sources and empirical evidence, while providing a very broad historical, sociological, political and economic perspective. The other two authors assume a journalistic approach, or, in other words, a narrative and anecdotal approach, thanks to which they give us, something that is absent in Piketty's work: the concrete human dimension of inequality, which often assumes lacerating and extremely painful characteristics.
Keywords: Social Science; Economy